2017
DOI: 10.1080/13557858.2017.1315378
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination and depressive symptoms among US Latinos: the modifying role of educational attainment

Abstract: Objective Despite growing evidence that discrimination may contribute to poor mental health, few studies have assessed this association among US Latinos. Furthermore, the interaction between discrimination and educational attainment in shaping Latino mental health is virtually unexplored. This study aims to examine the association between perceived discrimination and depressive symptoms and the modifying role of education among a population of Mexican-origin adults. Design We utilized population-based data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 74 publications
1
34
0
Order By: Relevance
“…Lower DASS-21 scores in individuals with higher education levels also support the findings of a previous study, suggesting a lower risk of depressive disorder among well-educated subjects [40]. A large population-based survey in China highlighted that education level influenced depression or anxiety risk [41] albeit the presence of intermediary variables between education and negative percepts, such as occupational factors [42] or discrimination [43]. Subjects with low levels of education potentially have a greater inclination toward anxiety [44] because they may struggle to understand information about the pandemic.…”
Section: Discussionsupporting
confidence: 83%
“…Lower DASS-21 scores in individuals with higher education levels also support the findings of a previous study, suggesting a lower risk of depressive disorder among well-educated subjects [40]. A large population-based survey in China highlighted that education level influenced depression or anxiety risk [41] albeit the presence of intermediary variables between education and negative percepts, such as occupational factors [42] or discrimination [43]. Subjects with low levels of education potentially have a greater inclination toward anxiety [44] because they may struggle to understand information about the pandemic.…”
Section: Discussionsupporting
confidence: 83%
“…Notably, stigma has been examined as a factor for depression [ 21 ]. Numerous studies have indicated stigma as a cause of or an exacerbating variable in depression, including sexual orientation [ 22 ] weight [ 23 ], HIV/AIDS [ 24 , 25 ], race and ethnicity [ 26 , 27 , 28 , 29 ], disability [ 30 ], and citizenship status [ 31 ]. Anticipated stigma surrounding mental health can be a cause for delaying, avoiding or disengaging in treatment [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews reveal the strongest associations for harmful health effects are across a range of mental health outcomes including psychological distress, mental illness such as depression and anxiety, and suicidal ideation 1,2 , with poor mental health as a consequence of discrimination seen among Black 3,4 , Latino 5,6 , Asian/ Pacific Islander 7,8 , American Indian 9 , Middle Eastern/Arab 10 , and White communities 11 . Factors influencing mental health impacts include coping style, sex, socioeconomic class, educational attainment, and racial/ethnic group affiliation 1,5,12 . One potential mechanism underlying the perceived discrimination-health relationship is allostatic load developed by heighted stress responses and negative emotional states from experiences of discrimination.…”
Section: Introductionmentioning
confidence: 99%